The definite article in Votic: the process of grammaticalisation - Tatiana Agranat (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2015)
The paper is devoted to the grammaticalisation of the deictic pronoun se into a definite article in Votic. The author traces this process diachronically demonstrating the results of her studies with the examples of a folktale written down by August Ahlqvist in the middle of the 19th century, and of a text written down by herself at the beginning of the 21st century. The reason for article-like usage of se in Votic narrative in the 19th century seems to be the same as in Finnish narratives in the 19th century, as we can judge from Laury (1991): NPs that are prefaced with se have references that are important in some way for the narrative. In modern Votic se lost its function of marking NPs as prominent and became the marker of identifiability. The author draws the conclusion that the grammaticalisation of se in Votic is not yet completed, because se is not compulsory.